2013
DOI: 10.1161/circgenetics.112.964619
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Association Study Identifies Novel Loci Associated With Concentrations of Four Plasma Phospholipid Fatty Acids in the De Novo Lipogenesis Pathway

Abstract: Background Palmitic acid(16:0), stearic acid(18:0), palmitoleic acid(16:1n-7), and oleic acid(18:1n-9) are major saturated and mono-unsaturated fatty acids that affect cellular signaling and metabolic pathways. They are synthesized via de novo lipogenesis (DNL) and are the main saturated and mono-unsaturated fatty acids in the diet. Levels of these fatty acids have been linked to diseases including type 2 diabetes and coronary heart disease. Methods and Results Genome-wide association studies were conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
95
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 93 publications
(107 citation statements)
references
References 64 publications
5
95
4
Order By: Relevance
“…Our analyses support the presence of these haplotypes in this sample, as well as the finding that the more common haplotype is associated with increased efficiency of long-chain fatty acid synthesis [47]. Furthermore, these genes have been shown to be associated with a number of phenotypes in SNP association studies, including certain plasma fatty acids [48,49], plasma lipoproteins [48,50], and response to lipid therapy [51] as well as DNA methylation levels [52]. …”
Section: Resultssupporting
confidence: 77%
“…Our analyses support the presence of these haplotypes in this sample, as well as the finding that the more common haplotype is associated with increased efficiency of long-chain fatty acid synthesis [47]. Furthermore, these genes have been shown to be associated with a number of phenotypes in SNP association studies, including certain plasma fatty acids [48,49], plasma lipoproteins [48,50], and response to lipid therapy [51] as well as DNA methylation levels [52]. …”
Section: Resultssupporting
confidence: 77%
“…Adjustment for fatty acid biomarkers of de novo lipogenesis, 16:0 and 18:0, 25, 26 had the greatest effect on plasma 15:0, which was no longer significantly associated with diabetes when 16:0 and 18:0 were removed as covariates (continuous HR=1.10, 95%CI=0.85–1.42). Conversely, removal of these fatty acid covariates had smaller influence on associations with diabetes for plasma 17:0 (HR=0.67, 95%CI=0.51–0.89) or t-16:1n-7 (HR=0.68, 95%CI=0.51–0.92).…”
Section: Resultsmentioning
confidence: 97%
“…Hepatic GCK mRNA expression is positively associated with lipogenic gene expression [FAS, acetylCoA carboxylase (ACC)] and with the de novo lipogenesis index ( 29 ). A GWAS showed that the GCKR rs780093 SNP [of which the minor allele is in strong linkage disequilibrium with the minor allele of rs1260326 ( 30 )] is associated with increased de novo lipogenesis ( 31 ). LC-PUFAs [mainly DHA ( 32 )] may act by downregulating FAS activation both directly ( 33 ) and by inhibiting sterol regulatory element-binding protein ( 34,35 ) and carbohydrate responsive element-binding protein.…”
Section: Discussionmentioning
confidence: 99%